Mirepoix: extração e estruturação de aromáticos voláteis para uso gastronômico - Mota, Robson Nascimento da (2023)
Aromatic preparations have the purpose of inserting flavor, aroma and color to indistinct sweet and savory gastronomic preparations, providing increased taste sensation. They are elaborated with the use of various ingredients, among them stand out vegetables, vegetables, herbs, spices, edible fungi, lipids and sometimes acids. The object of the research was to develop a structured bar with hydrocolloides without the use of artificial additives. In the first part, the exploratory stage, the main works of gastronomic literature were consulted, but above all available articles, presenting, at the end, a review on the main aromatic preparations used in gastronomy, emphasizing mirepoix. The experimental stage consisted of two stages: in the first one were identified as, por gas chromatography coupled to mass spectrometry, the main compounds present in the in natura insums, which are part of this aromatic preparation, individually, as well as in the mirepoix itself. In the second stage, the product was developed using freeze-dried methods, Soxhlet extraction and gelling, technologies already widely used in foodstuffs. The end of the experiment culminated in the development of a bar structured with hydrocolóides, without the use of artificial additives, keeping the sensory characteristics close to those when in natura. After product development, a market research was carried out, being applied 135 questionnaires and targeting teachers and gastronomy professionals, seeking to identify the possible acceptance of this product, being possible to confirm the acceptance of a new aromatic product without adding artificial additives, by the interviewees.